2018
DOI: 10.3847/1538-4357/aaa66e
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Observations of the Outflowing Wind in the Lensed Quasar SDSS J1001+5027

Abstract: We performed spectroscopic observations of the small-separation lensed quasar SDSS J1001+5027, whose images have an angular separation θ = 2. ′′ 86, and placed constraints on the physical properties of gas clouds in the vicinity of the quasar (i.e., in the outflowing wind launched from the accretion disk). The two cylinders of sight to the two lensed images go through the same region of the outflowing wind and they become fully separated with no overlap at a very large distance from the source (∼330 pc). We di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 101 publications
0
1
0
Order By: Relevance
“…The line-locking, observational signature of the velocity separation between distinct absorption components, similar to the velocity splitting of an absorption doublet and/or multiplet, was reported as early as the 1970s, not long after the discovery of quasars (e.g., Williams et al 1975;Coleman et al 1976;Adams et al 1978;Perry et al 1978). Since then, the line-locking signatures in narrow absorption lines (NALs; absorption widths of less than 500 km s −1 ) have been largely identified in both broad absorption line (BAL) quasars (absorption widths of at least 2000 km s −1 ) and non-BAL quasars (e.g., Foltz et al 1987;Borra et al 1996;Tripp et al 1997;Srianand 2000;Srianand & Petitjean 2000;Vilkoviskij & Irwin 2001;Srianand et al 2002;Ganguly et al 2003;Fechner et al 2004;Gallagher et al 2004;Benn et al 2005;Misawa et al 2007Misawa et al , 2013Misawa et al , 2014Misawa et al , 2016Misawa et al , 2018Simon & Hamann 2010;Hamann et al 2011;Bowler et al 2014). Of particular note is a systematic study by Bowler et al (2014) that showed evidence for line-locking signatures in almost two-thirds of quasars possesses multiple C IV absorption systems, based on a sample of about 34,000 quasar spectra (Schneider et al 2010) from the Sloan Digital Sky Survey (SDSS; York et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The line-locking, observational signature of the velocity separation between distinct absorption components, similar to the velocity splitting of an absorption doublet and/or multiplet, was reported as early as the 1970s, not long after the discovery of quasars (e.g., Williams et al 1975;Coleman et al 1976;Adams et al 1978;Perry et al 1978). Since then, the line-locking signatures in narrow absorption lines (NALs; absorption widths of less than 500 km s −1 ) have been largely identified in both broad absorption line (BAL) quasars (absorption widths of at least 2000 km s −1 ) and non-BAL quasars (e.g., Foltz et al 1987;Borra et al 1996;Tripp et al 1997;Srianand 2000;Srianand & Petitjean 2000;Vilkoviskij & Irwin 2001;Srianand et al 2002;Ganguly et al 2003;Fechner et al 2004;Gallagher et al 2004;Benn et al 2005;Misawa et al 2007Misawa et al , 2013Misawa et al , 2014Misawa et al , 2016Misawa et al , 2018Simon & Hamann 2010;Hamann et al 2011;Bowler et al 2014). Of particular note is a systematic study by Bowler et al (2014) that showed evidence for line-locking signatures in almost two-thirds of quasars possesses multiple C IV absorption systems, based on a sample of about 34,000 quasar spectra (Schneider et al 2010) from the Sloan Digital Sky Survey (SDSS; York et al 2000).…”
Section: Introductionmentioning
confidence: 99%